A DM1-doped porous gold nanoshell system for NIR accelerated redox-responsive release and triple modal imaging guided photothermal synergistic chemotherapy - Pengcheng Xu; Ru Wang; Wenqian Yang; Yanyan Liu; Dongsheng He; Zixuan Ye; Daquan Chen; Yuan Ding; Jiasheng Tu; Yan Shen (Journal of Nanobiotechnology, 2021)
Abstract Background Although many treatments for breast cancer are available, poor tumour targeting limits the effectiveness of most approaches. Consequently, it is difficult to achieve satisfactory results with monotherapies. The lack of accurate diagnostic and monitoring methods also limit the benefits of cancer treatment. The aim of this study was to design a nanocarrier comprising porous gold nanoshells (PGNSs) co-decorated with methoxy polyethylene glycol (mPEG) and trastuzumab (Herceptin®, HER), a therapeutic monoclonal antibody that binds specifically to human epidermal receptor-2 (HER2)-overexpressing breast cancer cells. Furthermore, a derivative of the microtubule-targeting drug maytansine (DM1) was incorporated in the PGNSs. Methods Prepared PGNSs were coated with mPEG, DM1 and HER via electrostatic interactions and Au–S bonds to yield DM1-mPEG/HER-PGNSs. SK-BR-3 (high HER2 expression) and MCF-7 (low HER2) breast cancer cells were treated with DM1-mPEG/HER-PGNSs, and cytotoxicity was evaluated in terms of cell viability and apoptosis. The selective uptake of the coated PGNSs by cancer cells and subsequent intracellular accumulation were studied in vitro and in vivo using inductively coupled plasma mass spectrometry and fluorescence imaging. The multimodal imaging feasibility and synergistic chemo-photothermal therapeutic efficacy of the DM1-mPEG/HER-PGNSs were investigated in breast cancer tumour-bearing mice. The molecular mechanisms associated with the anti-tumour therapeutic use of the nanoparticles were also elucidated. Result The prepared DM1-mPEG/HER-PGNSs had a size of 78.6 nm and displayed excellent colloidal stability, photothermal conversion ability and redox-sensitive drug release. These DM1-mPEG/HER-PGNSs were taken up selectively by cancer cells in vitro and accumulated at tumour sites in vivo. Moreover, the DM1-mPEG/HER-PGNSs enhanced the performance of multimodal computed tomography (CT), photoacoustic (PA) and photothermal (PT) imaging and enabled chemo-thermal combination therapy. The therapeutic mechanism involved the induction of tumour cell apoptosis via the activation of tubulin, caspase-3 and the heat shock protein 70 pathway. M2 macrophage suppression and anti-metastatic functions were also observed. Conclusion The prepared DM1-mPEG/HER-PGNSs enabled nanodart-like tumour targeting, visibility by CT, PA and PT imaging in vivo and powerful tumour inhibition mediated by chemo-thermal combination therapy in vivo. In summary, these unique gold nanocarriers appear to have good potential as theranostic nanoagents that can serve both as a probe for enhanced multimodal imaging and as a novel targeted anti-tumour drug delivery system to achieve precision nanomedicine for cancers.